Escaping darkness - Jenkins, Jerry B.; Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House Publishers, 2006)
Twins Ashley and Bryce get involved in another mystery when they observe strange goings-on near the alpaca farm, and, meantime, their school is embroiled in a controversy over an annual day of public prayer.
4.5
3-6
Keywords: Christian life -- Fiction; Drug dealers -- Fiction; Illegal aliens -- Fiction; Mystery and detective stories; Schools -- Fiction; Twins -- Fiction; Christian life -- Fiction; Drug dealers -- Fiction; Illegal aliens -- Fiction; Mystery fiction; School stories; Twins -- Fiction; Colorado -- Fiction; Colorado -- Fiction